Enhancing the functionality of cotton fabric by physical and chemical pre-treatments: A comparative study. (20th August 2016) - Gargoubi, Sondes; Tolouei, Ranna; Chevallier, Pascale; Levesque, Lucie; Ladhari, Neji; Boudokhane, Chedly; Mantovani, Diego
Highlights: Dyeing is a competitive and a cost-effective process to generate functional finishing for textiles. Amination pre-treatments overcome the low uptake of natural functional dye on the natural carbohydrate polymer surface. A higher color fastness was successfully obtained by surface modification using dopamine. The mechanical properties were not affected by amination pre-treatments. Abstract: Recently, antimicrobial and decontaminating textiles, such as cotton a natural carbohydrate polymer, are generating more attention. Plant materials used for natural dyes are expected to impart biofunctional properties and high added valued functional textiles. In the current study, surface modification of cotton to maximize the dye amount on the surface has been investigated. Physical modification using nitrogen-hydrogen plasma, chemical modification using chitosan and chemical modification using dopamine as biopolymers imparting amino groups were explored. Furthermore, dye exhaustion of curcumin, as a natural functional dye has been studied. Dye stability tests were also performed after fabric washing using hospital washing protocol to predict the durability of the functionalizations. The results demonstrated that cotton surfaces treated with dopamine exhibit a high level of dye uptake (78%) and a good washing fastness. The use of non-toxic and natural additives during cotton finishing process could give the opportunity of cradle to cradle design for antimicrobial textile industries.